PENGARUH KOMUNITAS BEAUTY CREATOR DALAM MEMBENTUK TREN MAKEUP DI DENPASAR BALI - Sari, Intan Purnama; Wiasti, Ni Made; Suarsana, I Nyoman (FISIP Universitas Malikussaleh, 2024)
Beauty creators are individuals who create and set trends in the field of beauty content through various media forms such as writing, videos, and photos, which are uploaded on popular platforms. One well-known Beauty creator community is Bali Beauty Blogger, where like-minded Beauty creators gather to create beauty content in various formats, including writing, videos, and photos, which are shared on platforms such as blogs, TikTok, Instagram, and YouTube. In the digital era and social media landscape, Beauty creators play a significant role in shaping beauty trends and preferences among the millennial generation. By understanding the profile of Beauty creator communities and their strategies, this research aims to provide insights into how they influence and become trendsetters in Denpasar city. The research adopts a qualitative approach, gathering primary data through observation and interviews, and secondary data through documents, literature, and other texts. The data is analyzed using qualitative analysis methods to present the findings and draw conclusions. The results of the research indicate that the growing community in Denpasar city is Bali Beauty Blogger, a Beauty creator community focusing on beauty content creation. Its members actively produce written, video, and photo content uploaded on various platforms such as blogs, TikTok, Instagram, and YouTube. The community serves as a platform for young Beauty creators in Bali to express their creative ideas in the field of beauty. The research also reveals that Bali Beauty Blogger has a vision to connect brands with the public through brand awareness, and they employ various strategies to sustain their presence.